2014
DOI: 10.1016/j.neuron.2014.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Extrasynaptic NMDA Receptor Involvement in Central Nervous System Disorders

Abstract: NMDA receptor (NMDAR)-induced excitotoxicity is thought to contribute to the cell death associated with certain neurodegenerative diseases, stroke, epilepsy, and traumatic brain injury. Targeting NMDARs therapeutically is complicated by the fact that cell signaling downstream of their activation can promote cell survival and plasticity as well as excitotoxicity. However, research over the past decade has suggested that overactivation of NMDARs located outside of the synapse plays a major role in NMDAR toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
411
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(427 citation statements)
references
References 173 publications
(246 reference statements)
9
411
1
6
Order By: Relevance
“…Ketamine is an open-channel NMDA receptor blocker, and is therefore theoretically more selective for extrasynaptic NMDA receptors, since these spend longer in the 'open' configuration because of a more tonic activation by extrasynaptic glutamate. Extrasynaptic NMDA receptors are known to induce long-term depression and are linked to neuronal inefficiency mechanisms (30)(31)(32), and their selective antagonism can be expected to increase neuronal activity. Indeed, it has been shown that systemically injected ketamine induces an acute (within 20 min) increase in extracellular glutamate levels in the frontal cortex of rats (33), which may be an indication of increased glutamate overflow from synapses due to enhanced neuronal firing.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is an open-channel NMDA receptor blocker, and is therefore theoretically more selective for extrasynaptic NMDA receptors, since these spend longer in the 'open' configuration because of a more tonic activation by extrasynaptic glutamate. Extrasynaptic NMDA receptors are known to induce long-term depression and are linked to neuronal inefficiency mechanisms (30)(31)(32), and their selective antagonism can be expected to increase neuronal activity. Indeed, it has been shown that systemically injected ketamine induces an acute (within 20 min) increase in extracellular glutamate levels in the frontal cortex of rats (33), which may be an indication of increased glutamate overflow from synapses due to enhanced neuronal firing.…”
Section: Discussionmentioning
confidence: 99%
“…PSD-95 is normally enriched on synaptic membranes, but it can also be found on extrasynaptic membranes in the mouse model of Huntington's disease (Fan et al 2012;Zheng et al 2011). GluN2B-containing NMDArs are very mobile, moving easily between synaptic and extrasynaptic membranes (Groc et al 2006;Parsons and Raymond 2014). We hypothesized that there may be an aging effect on the membrane localization of NMDArs and their effector proteins.…”
Section: Age-related Changes In Glun2 Proteinsmentioning
confidence: 99%
“…In fact, GluN2B is the most prominent tyrosine phosphorylated protein within postsynaptic densities (PSDs) (14), and phosphorylation is increased during long-term potentiation (LTP) in CA1 hippocampus (15). Moreover, tyrosine phosphorylation of GluN2B has been shown to increase in several pathological conditions, including ischemia and seizures (16)(17)(18)(19).Striatal-enriched protein tyrosine phosphatase (STEP, also known as "PTPN5") is a brain-specific protein phosphatase that is expressed in the striatum, hippocampus, and cortex (20, 21). The STEP family of protein tyrosine phosphatases includes both membrane-associated [striatal-enriched protein tyrosine phosphatase 61 (STEP 61 )] and cytosolic (STEP 46 ) variants that are generated by alternative splicing of a single gene (22-24).…”
mentioning
confidence: 99%
“…In fact, GluN2B is the most prominent tyrosine phosphorylated protein within postsynaptic densities (PSDs) (14), and phosphorylation is increased during long-term potentiation (LTP) in CA1 hippocampus (15). Moreover, tyrosine phosphorylation of GluN2B has been shown to increase in several pathological conditions, including ischemia and seizures (16)(17)(18)(19).…”
mentioning
confidence: 99%